Comparative political journalism in South America: Professional configurations and disputes over truth in Argentina, Brazil, and Uruguay - Schuliaquer, Ivan (2024)
This article analyzes the (re)configurations of political journalism in the face of the challenges of the contemporary information-communication ecosystem, political polarization, and disputes over the truth. It employs interviews, observations, and literature review to develop an unique model for comparative analysis of political journalism, applied to Argentina, Brazil, and Uruguay. The results indicate that, despite remaining continuities in the Latin American region, the characteristics of political journalism vary significantly between countries, impacting public debate. In Uruguay and Brazil, efforts are made to contain misinformation, while in Argentina, it is sometimes perpetuated by the journalists themselves.